2013
DOI: 10.1007/s11010-013-1669-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-alanine administration on selected parameters of oxidative stress and phosphoryltransfer network in cerebral cortex and cerebellum of rats

Abstract: β-Alanine is a β-amino acid derivative of the degradation of pyrimidine uracil and precursor of the oxidative substrate acetyl-coenzyme A (acetyl-CoA). The accumulation of β-alanine occurs in β-alaninemia, an inborn error of metabolism. Patients with β-alaninemia may develop neurological abnormalities whose mechanisms are far from being understood. In this study we evaluated the effects of β-alanine administration on some parameters of oxidative stress and on creatine kinase, pyruvate kinase, and adenylate kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Gemelli et al [9] proposed that oxidative stress might contribute to the symptoms of hyper-beta-alaninemia. A major source of superoxide production in the cytosol of most cells is NADPH oxidase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gemelli et al [9] proposed that oxidative stress might contribute to the symptoms of hyper-beta-alaninemia. A major source of superoxide production in the cytosol of most cells is NADPH oxidase.…”
Section: Resultsmentioning
confidence: 99%
“…Gemelli et al [9] have suggested that the neurotoxicity might be caused by oxidative stress. In β-alanine-treated rats, they observed an increase in catalase activity of the cerebral cortex and cerebellum and a reduction in the activity of superoxide dismutase, which together are capable of elevating H 2 O 2 and superoxide anion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Mathers et al (34) has recently shown that chemical transmission at the inhibitory synapses in the thalamus involves receptor activation by β-alanine. The importance of β-alanine for synaptic transmission is supported by the fact that the patients with β-alaninemia (accumulation of β-alanine as inborn error of metabolism) may develop neurological abnormalities whose mechanisms are far from being understood (35). …”
Section: Discussionmentioning
confidence: 99%
“…Adenylate kinase (AK) (EC 2.7.4.3) catalyzes the reversible phosphoryl transfer between ATP and AMP [11,12]. This enzyme, along with creatine kinase (CK) (EC 2.7.3.2), hexokinase (HK) (EC 2.7.1.1), and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) (EC 1.2.1.12), is responsible for the enzymatic phosphoryl transfer network or, in other words, responsible for the transfer of the phosphoryl of ATP where it is produced (mainly in the mitochondrial) to the place where it is consumed (mainly in the cytosol) [12].…”
Section: Introductionmentioning
confidence: 99%